Digital Business Business Algorithms, Cloud Computing and Data Engineering - Patnaik, Srikanta; Yang, Xin-She; Tavana, Madjid; Popentiu-Vlădicescu, Florin; Qiao, Feng (Lecture Notes on Data Engineering and Communications Technologies, 2019)
XV, 480 p. 111 illus., 77 illus. in color.